Board Characteristics and Earnings Per Share of Malaysian Islamic Banks - Shittu, Isah; Ahmad, Ayoib Che; Ishak, Zuaini (International Journal of Economics and Financial Issues, 2016)
Board characteristics of the corporate organization represent an important aspect of corporate monitoring. This study examined the effects of board size, the size of shariah supervisory board SSB and shariah board members meeting on the earnings per share of the Malaysian Islamic banks. The study used data from sixteen (16) full-pledged Islamic banks in Malaysia for six year period (2010-2015). The study used Pool Ordinary Least Square OLS to estimate the regression after satisfying post -estimation tests. The results reveal significance positive relationship between board size, shariah board meeting and EPS at 1% level of significance. On the other hand, a negative relationship was found between shariah board size and EPS. The negative relationship between SSB size and EPS could be due to non-disclosure of the minimum number of shariah board members by some banks. Keywords: board characteristics, Islamic banks, Malaysia JEL Classifications: M40; M41; M48